Develop the Enabling Environment for Innovative Entrepreneurship - Dumi, Alba; Maliqi, Gelina (Mediterranean Journal of Social Sciences, 2011)
E-Learning is gaining significant interest in distance education, including university and other. It also get a special importancein terms of exchanges of experiences between different institutions within and outside the country. Despite the distance people already havethe opportunity to learn from others, or used in any other time and place that they are. These advantages are powered by technologicaldevelopments, developments that require a generation as qualified to be adopted in time with the rapid technologicevolutions.The advantages of using e-learning are related to the degree of qualification of the generation which live in an era of rapid technologicalchange. Despite the rapid technological development in many countries there are benefits from the use of e-learning or there are benefits thatare not at levels as it’s required .E-learning will be consider as one of the new business that requires the implementation of a moderninfrastructure for the needs of customers .In determination of the needs customers there is always a question, which is necessary byenterprises in the e-learning to identify the application, create and determine its size.